What Has Happened to Labor Subcontracting? (Observatorio Económico, 2013)
In the Chilean collective unconscious, speaking of labor subcontracting is immediately associated with precariousness and conflict. In that sense, the most recent law, enacted in 2007, is a response to those problems, since it aims at better monitoring of compliance with the contractor firm's labor obligations and establishes minimum responsibilities for the principal firm in matters of hygiene, safety, and risk prevention. Many years after the rule was implemented, it is worth asking how this practice has evolved in recent years and whether any effect has been perceived. Continue reading...
Keywords: Labor subcontracting; Productivity; Precariousness